The Nature and Archaic Origins of Lifelong Learning Processes: The Relevance of Anthropology to Adult Education - Donovan Plumb (Adult Education Research Conference, 2006)
Contemporary anthropology is developing key perspectives on human learning that are very relevant for the theories and practices of adult education. This paper explores the work of Merlin Donald, Donald Mithen, Michael Tomasello and Tim Ingold to show how current thinking in anthropology challenges the cognitivist bias that currently dominates our field.
Keywords: anthropology; human evolution; culture; situated learning